2013
DOI: 10.1371/journal.pone.0072475
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cu(II) on Oxidized Multi-Walled Carbon Nanotubes in the Presence of Hydroxylated and Carboxylated Fullerenes

Abstract: The adsorption of Cu(II) on oxidized multi-walled carbon nanotubes (oMWCNTs) as a function of contact time, pH, ionic strength, temperature, and hydroxylated fullerene (C60(OH)n) and carboxylated fullerene (C60(C(COOH)2)n) were studied under ambient conditions using batch techniques. The results showed that the adsorption of Cu(II) had rapidly reached equilibrium and the kinetic process was well described by a pseudo-second-order rate model. Cu(II) adsorption on oMWCNTs was dependent on pH but independent of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 56 publications
5
26
0
Order By: Relevance
“…Kosa et al used MWCNT modified with 8-hydroxyquinoline and they reached 100% of Cu (II) adsorption efficiency and 0.080 mg/g of adsorption uptake [19]. Wang et al prepared oxidized multi-walled carbon nanotubes in the presence of hydroxylated and carboxylated fullerenes, and they found the Cu (II) ion uptake as 33.97 mg/g [20]. Sitko et al used another carbonaceous material, graphene oxide for heavy metal adsorption.…”
Section: Investigation Of Adsorption Equilibrium Isothermsmentioning
confidence: 99%
“…Kosa et al used MWCNT modified with 8-hydroxyquinoline and they reached 100% of Cu (II) adsorption efficiency and 0.080 mg/g of adsorption uptake [19]. Wang et al prepared oxidized multi-walled carbon nanotubes in the presence of hydroxylated and carboxylated fullerenes, and they found the Cu (II) ion uptake as 33.97 mg/g [20]. Sitko et al used another carbonaceous material, graphene oxide for heavy metal adsorption.…”
Section: Investigation Of Adsorption Equilibrium Isothermsmentioning
confidence: 99%
“…Similarly, the band showing the presence of C�O groups in -COOH appears at around 1627 cm −1 . Wang et al [22], Li et al [25], and Moosa et al [30] found similar characteristic bands for the surface-modified CNTs.…”
Section: Characterization Of the Materialmentioning
confidence: 74%
“…erefore, the removal of copper from water is an essential study. Regarding the removal of Cu(II) with CNTs, many studies conducted so far have shown comparatively low values of maximum Cu(II) adsorption capacity [22][23][24][25][26][27][28]. e carbon nanotubes are known as an excellent adsorbent for heavy metals [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the -stacking between aromatic structure of dyes and sp 2 regions of R-GO, as well as the electrostatic interactions between charged organics or metal ions and the surface oxygen-containing groups of R-GO might also assist in the adsorption. 33,34 As is well-known, the interaction …”
Section: Adsorption Properties Of R-go/r-rgomentioning
confidence: 99%
“…34 Therefore, compared with R-RGO, the more C structure of the R-GO made it have a larger maximum adsorption amount for gallic acid, but the less surface area made its adsorption rate decrease.…”
Section: -6mentioning
confidence: 99%